Modeling and Investigation of the Influential Reinforcement Parameters on the Strength of Polypropylene Lignocellulosic Fiber Composites Using Analysis of Variances and Box-Cox Transformation Technique - Mu’ayyad M. Al-Shrida; Mohammed T. Hayajneh; Faris M. AL-Oqla (Materials Research, 2023)
Green materials have received great interest in wide industrial applications due to their desired properties. However, the reinforcing conditions have a significant impact on how they perform in their final use. The current study intends to statistically examine the effects of three key parameters on the average tensile strength of polypropylene composites. These factors included the type of fiber, the chemical treatment, and the fiber's weight percentage. The fibers were hemp and sisal, and the weight percentages were 10, 20, and 30. While some of them received sodium hydroxide (NaOH) treatment, the rest were left untreated. The main effect and the interaction effect were both examined using the analysis of variance (ANOVA). The findings demonstrated that, on average, the weight percentage had no tangible effect on the tensile strength of polypropylene (PP) composites. Additionally, the performance of sisal and hemp composites was unaffected by treatment. The strength, however, is significantly influenced by the type of fiber. The investigation also showed that there was little difference between untreated hemp and untreated sisal in terms of tensile strength.